Mechanical Analysis of the Ring Opening Test Applied to Human Ascending Aortas - Garcia-Herrera, C; Ortega-Aguilera, R (Taylor and Francis Ltd., 2016)
This work presents experiments, modelling and numerical simulation aimed at describing the mechanical response of human ascending aortas in the ring opening test. The objective is to quantify, from the opening angles measured in the test, the residual stress distribution along the artery wall and, afterwards, how this stress pattern changes when the artery is subjected to standard physiological pressures. The cases studied correspond to four groups including both healthy and pathological arteries. The tissues are characterized via tensile test measurements that enable to derive the material parameters of two constitutive models adopted in the present analysis. Overall, the numerical results obtained for all groups were found to be a useful data that allow to estimate the residual stress and their influence on the vessels under normal and hypertension physiological conditions. © 2016 Informa UK Limited, trading as Taylor & Francis Group.